PERTUMBUHAN DAN KADAR HARA NPK TANAMAN KELAPA SAWIT DENGAN DAN TANPA APLIKASI DECANTER SOLID - wahyu tri patria; Teguh Randi Pradana; Albertus Fajar Irawan; Nuni Gofar (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2022)
Oil palm is a widely cultivated plantation crop in Indonesia. Oil palm production is influenced by fertilizers. One of the organic wastes that can be used as fertilizer is a solid decanter. The purpose of this study was to determine the differences in growth and nutrient content of N, P and K in plants with solid decanters and those not. The research was carried out from October 2019 to March 2020 at PT. Sampoerna Agro Tbk, Mesuji Garden, Mesuji District, Ogan Komering Ilir Regency, South Sumatra. This study uses the t test with independent samples. Samples of oil palm plants used are immature oil palm plants (TBM) aged 2 years in blocks 13A and 18A which have been fertilized by NPK according to recommendations and in block 13A have been given a solid decanter of 15 tons ha-1. The results showed that plants that were applied solid decanter gave a significant difference response to plants that were not given solid decanter on the variable number of leaves, number of midribs and plant height and on nutrient levels of P and K with t test values of 0.001, 0.000, and 0.003 for variables growth and 0.006 and 0.000 in nutrient content variables. Based on the physical form, it also shows that plants that have solid decanter application have better shape, size and plant freshness than plants that are not applied with solid decanter. Oil palm is a widely cultivated plantation crop in Indonesia. Oil palm production is influenced by fertilizers. One of the organic wastes that can be used as fertilizer is a solid decanter. The purpose of this study was to determine the differences in growth and nutrient content of N, P and K in plants with solid decanters and those not. The research was carried out from October 2019 to March 2020 at PT. Sampoerna Agro Tbk, Mesuji Garden, Mesuji District, Ogan Komering Ilir Regency, South Sumatra. This study uses the t test with independent samples. Samples of oil palm plants used are immature oil palm plants (TBM) aged 2 years in blocks 13A and 18A which have been fertilized by NPK according to recommendations and in block 13A have been given a solid decanter of 15 tons ha-1. The results showed that plants that were applied solid decanter gave a significant difference response to plants that were not given solid decanter on the variable number of leaves, number of midribs and plant height and on nutrient levels of P and K with t test values of 0.001, 0.000, and 0.003 for variables growth and 0.006 and 0.000 in nutrient content variables. Based on the physical form, it also shows that plants that have solid decanter application have better shape, size and plant freshness than plants that are not applied with solid decanter. Keywords: Oil palm, Decanter Solid, Growth, Nutrient Content